Effects of a 14-week golf-specific strength training program on pelvic rotational velocity and ball impact position using the K-Vest: A case report - Ghigiarelli, J.; Gerland, R.; Cerra, N. (International Journal of Golf Science, 2015)
The purpose of this case study was to examine the effects of a golf-specific strength-training program on pelvic rotational velocity and pelvis and upper body torso position at ball impact position. One middle-aged male recreational golfer (42 years, handicap 25) completed a 14-week strength-training program. Swing analysis was tested at Weeks 1, 8, and 14 using a biofeedback 3D motion analysis system. A significant increase of 6% in pelvic rotational velocity occurred between midtest and posttest (pre = 393 ± 6.8°, mid = 377 ± 10.6°, post = 418 ± 9.9°). However, swing mechanics at impact position worsened, which is likely due to the lack of practice time and/or lack of technical instruction. A golf-specific strength-training program that targets rotational power will improve pelvic rotational velocity. In low-skilled golfers, however, proper technical instruction is needed to observe an improvement in body position at ball impact.